(untitled) (The Planet, 2023)
Background: Among the most common problems inmodern intensive care units is having trouble getting off ofartificial ventilation. The diaphragm is a key muscle forbreathing, and problems with it may be very common inpeople who need motorized ventilation. Long-termmechanical breathing and inability to wean are linked todiaphragm dysfunction. Objectives: The goal of thisresearch was to establish whether or not a higherdiaphragm thickening fraction is a reliable indicator of asmooth transition away from mechanical ventilation.Methods: This observational study was performed among89 critically ill patients on mechanical ventilation for 48hours who planned for weaning in the ICU at theDepartment of Anaesthesia, Analgesia, Palliative andIntensive Care Medicine, Dhaka Medical College Hospital,in Dhaka. The patients were all critically sick and had been on mechanical ventilation for atleast 48 hours. Results: DTF >30% was discovered in 38 (95.0%) patients in the successfulweaning group, while DTF 30% was detected in 46 (93.8%) patients in the failed weaninggroup, according to ultrasound findings of the diaphragm. Predicting weaning success with aDTF>30% had a sensitivity of 95.0% and a specificity of 93.8%. Likewise, its positive predictive value was 92.6% and its negative predictive value was 95.8%. Furthermore, thepercentage of accuracy was 94.3%. Conclusion: The results of the current experimentshowed that DTF was an efficient measure for successfully weaning patients off ofmechanical breathing